Essence and Content of Legal Settlement and Tax Amnesty - M. S. Syromiatnikova (Law and Safety)
The article is focused on defining the essence and content of legal settlement and tax amnesty. The main features and areas of applying legal settlement in various fields of law have been studied. The legal principles of reaching a legal settlement in civil, labor, tax and criminal procedural law have been studied. The author has suggested own definition of a legal settlement. The content of a legal settlement has been defined as the achievement of mutual concessions of the parties within the legal norms.